Algae-based approaches for Holistic wastewater management: A low-cost paradigm - Simranjeet Singh; Lav Singh; Vijay Kumar; Wahid Ali; Praveen C. Ramamurthy; Daljeet Singh Dhanjal; Nikhita Sivaram; Ruby Angurana; Joginder Singh; Vimal Chandra Pandey; Nadeem A. Khan (Chemosphere, 2023)

Synergistic lignin degradation between Phanerochaete chrysosporium and Fenton chemistry is mediated through iron cycling and ligninolytic enzyme induction. - Julian J.A. van der Made; Elizabeth A. Landis; Griffin T. Deans; Ruby A. Lai; Kartik Chandran (Science of The Total Environment, 2023)

Species tree analyses and speciation-based species delimitation support new species in the relict catfish family Diplomystidae and provide insights on recent glacial history in Patagonia - Carlos P. Muñoz-Ramírez; Nicole Colin; Cristian B. Canales-Aguirre; Aliro Manosalva; Ruby López-Rodríguez; Jeet Sukumaran; Konrad Górski (Molecular Phylogenetics and Evolution, 2023)

Insulin-like peptides and ovary ecdysteroidogenic hormone differentially stimulate physiological processes regulating egg formation in the mosquito Aedes aegypti - Kangkang Chen; Xiaoyi Dou; Jai Hoon Eum; Ruby E. Harrison; Mark R. Brown; Michael R. Strand (Insect Biochemistry and Molecular Biology, 2023)

Food Fermentation Technology: Examples of application in Malaysian Foods - Genevie Eleanor Ruby; Noor Azira Abdul Mutalib; Nurul Hanisah Juhari; Ungku Fatimah Ungku Zainal Abidin (Food and Humanity, 2023)

One-way coupling of E3SM with ADCIRC demonstrated on Hurricane Harvey - Benjamin Pachev; L. Ruby Leung; Tian Zhou; Clint Dawson (Natural Hazards, 2023)

Selection of priority emerging contaminants in surface waters of India, Pakistan, Bangladesh, and Sri Lanka - Mozim Shafi; Ruby Jan; Khalid Muzamil Gani (Chemosphere, 2023)

Electrochemical simultaneous determination of hydroquinone, catechol, bisphenol A, and bisphenol S using a novel mesoporous nickel-modified carbon sensor - Yilei Xue; Meissam Noroozifar; Ruby May A. Sullan; Kagan Kerman (Chemosphere, 2023)

Multidisiplinary design optimization of a power generation system based on waste energy recovery from an internal combustion engine using organic Rankine cycle and thermoelectric generator - Abdeljelil Chammam; Abhishek Kumar Tripathi; Abrahan-Pablo Aslla-Quispe; Yersi-Luis Huamán-Romaní; Sherzod Shukhratovich Abdullaev; Naseer Ali Hussien; Ahmed Alkhayyat; Ali hashim Alsalamy; Ruby Pant (Chemosphere, 2023)

Effect of different types of volatile fatty acids on the performance and bacterial population in a batch reactor performing biological nutrient removal - Ruby Diaz; Soklida Hong; Ramesh Goel (Bioresource Technology, 2023)

Unrivalled insight into potential biopharmaceutical application of Saussurea albescens (DC.) Sch.Bip.: Chemical profiling, antioxidant and enzyme inhibition activities and in silico studies - Muhammad Imran Tousif; Muhammad Saleem; Saba Tauseef; Mamona Nazir; Tahira Ruby; Reaz Uddin; Sharon Elaine D'souza; Muhammad Aleem Ashraf; Ghulam Mustafa Kamal; Jallat Khan; Gokhan Zengin (Biocatalysis and Agricultural Biotechnology, 2023)

Hydrolysate production from sugarcane bagasse using steam explosion and sequential steam explosion-dilute acid pretreatment for polyhydroxyalkanoate fermentation - Hazel Joy C. Barrameda; Princess J. Requiso; Catalino G. Alfafara; Fidel Rey P. Nayve Jr.; Ruby Lynn G. Ventura; Jey-R S. Ventura (Bioactive Carbohydrates and Dietary Fibre, 2023)

Belonging, identity and place: Middle-class Tasmanian rural young people in urban university - Sarah Castle; Ruby Grant (Journal of Rural Studies, 2023)

Influence of injection strategies on ignition patterns of RCCI combustion engine fuelled with hydrogen enriched natural gas - Akshay Loyte; Jiwak Suryawanshi; Girish Bhiogade; Yuvarajan Devarajan; Raja Thandavamoorthy; Ruby Mishra; Natrayan L (Environmental Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Seasonal drivers of dissolved oxygen across a tidal creek–marsh interface revealed by machine learning - Peter J. Regier; Nicholas D. Ward; Allison N. Myers‐Pigg; Jay Grate; Michael J. Freeman; Ruby N. Ghosh (Limnology and Oceanography, 2023)
Dissolved oxygen (DO) is a key biogeochemical control in coastal systems, and its concentration and drivers vary markedly through time and space. This makes it difficult to accurately represent coastal DO and associated biogeochemical processes in models, limiting our ability to predict how these systems will respond to global change. We obtained high‐frequency (5‐min) in situ measurements of DO collected at three locations across the interface of a tidal creek and coastal marsh in the Pacific Northwest, USA. Random Forest machine learning models quantified the importance of three categories of environmental drivers (Aquatic, Climatic, and Terrestrial) of DO variability across the creek–marsh interface. We selected two 4‐month datasets representing Summer and Winter seasonal periods to test two hypotheses on the dominant drivers of DO at the coastal interface. We found that the Terrestrial driver—characterized by long periods of anaerobic conditions and episodic pulses in DO after floods—was most important during the Winter, whereas the Aquatic driver—characterized by variability over tidal, diel, and lunar cycles—was most important during the Summer. We explored how future climate change scenarios could alter the drivers of DO variability using a cumulative sums driver–response framework. Our results suggest that under climate change, Aquatic and Climatic drivers may increase in importance during the Summer, potentially linked to changing metabolic regimes and sea level, with Terrestrial driver importance potentially increasing during the Winter. Our approach highlights useful methods for understanding the spatiotemporal complexity of oxygen across coastal interfaces and quantifying the relative importance of distinct environmental drivers.

Volatile fatty acid production from primary and secondary sludges to support efficient nutrient management - Ruby Diaz; Anjan Goswami; Herald C. Clark; Richard Michelson; Ramesh Goel (Chemosphere, 2023)

Measurement of lime movement and dissolution in acidic soils using mid-infrared spectroscopy - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Brian Hughes; Luke M. Mosley (Soil and Tillage Research, 2023)

Impact of precursors and bioaccessibility on childhood PFAS exposure from house dust - Albert L. Juhasz; Adam Keith; Ruby Jones; Farzana Kastury (Science of The Total Environment, 2023)

Glomus fasciculatum an arbuscular mycorrhizal fungus alleviate the adverse effects of lead, arsenic, nickel, and improves growth parameters of Monarda citriodora Cerv.ex Lag (lemon beebalm) - Savita Luxmi; Ruby Singh; Sajad Ahmed; Sumit G. Gandhi; Rajendra Bhanwaria (Rhizosphere, 2023)

Tropical cyclone strength, precipitation, and environment in variable resolution CAM-MPAS simulations over Western North Pacific - Yuan Liang; Ben Yang; Minghuai Wang; Yipeng Guo; Koichi Sakaguchi; L. Ruby Leung (Climate Dynamics, 2023)

The psychology of eating animals and veg*nism - Matthew B. Ruby; Hank Rothgerber; Christopher J. Hopwood (Appetite, 2023)

Metal/metal oxide-carbohydrate polymers framework for industrial and biological applications: Current advancements and future directions - Jeenat Aslam; Saman Zehra; Mohammad Mobin; M.A. Quraishi; Chandrabhan Verma; Ruby Aslam (Carbohydrate Polymers, 2023)

Atmospheric Microplastics: Perspectives on Origin, Abundances, Ecological and Health Risks - Shivali Gupta; Rakesh Kumar; Akanksha Rajput; Ruby Gorka; Antima Gupta; Nazuk Bhasin; Sudesh Yadav; Anju Verma; Kirpa Ram; Madulika Bhagat (Environmental Science and Pollution Research, 2023)

The vegan dilemma: Do peaceful protests worsen attitudes to veganism? - Rachel E. Menzies; Matthew B. Ruby; Ilan Dar-Nimrod (Appetite, 2023)

Overexpression of flowering locus D (FLD) in Indian mustard (Brassica juncea) enhances tolerance to Alternaria brassicae and Sclerotinia sclerotiorum - Shashi Shekhar; Ruby Panwar; Subhash Chandra Prasad; Deepak Kumar; Anjana Rustagi (Plant Cell Reports, 2023)

Effects of herbicides and mulch on the soil carbon, nitrogen, and microbial composition of two revegetated riparian zones over 3 years - Negar Omidvar; Steven M. Ogbourne; Zhihong Xu; Joanne Burton; Rebecca Ford; Babak Salehin; Iman Tahmasbian; Ruby Michael; Rachele Wilson; Shahla Hosseini Bai (Journal of Soils and Sediments, 2023)
Purpose Revegetation of riparian zones is important to improve their soil nitrogen (N) dynamics and to preserve their microbial compositions. However, the success of revegetation projects currently depends on weed control to reduce non-target vegetation competing over nutrients and to ensure the target plant species growth and survival. Different weed control methods affect soil microbial composition and N cycling. However, the long-term effects of herbicides on soil nitrogen (N) pools and microbial community composition remain uncertain even after cessation of the herbicide application. Materials and methods This study compared the impacts of different herbicides (Roundup ® , BioWeed™, Slasher ® , and acetic acid) with mulch on soil N dynamics and microbial community structure 3 years after vegetation establishment (herbicides applied repeatedly in the first 2 years after which no herbicides were applied in the third final year). Results and discussion Soil microbial biomass carbon (MBC) was significantly higher in mulch compared with Roundup ® , BioWeed™, Slasher ® , and acetic acid at month 26 at the Kandanga site and month 10 at the Pinbarren site. Soil MBC remained significantly higher in mulch compared with Roundup ® and BioWeed™, 12 months after the cessation of herbicide application at the Pinbarren site. Soil MBC in the Roundup ® and BioWeed™ groups was also lower than the acceptable threshold (160 mg kg −1 ) at month 34 at the Pinbarren site. Soil NO 3 − -N was significantly higher in the mulch than the Roundup ® at months 22 and 34 after revegetation at the Pinbarren site which could be partly explained by the decreased abundance of the denitrifying bacteria ( Candidatus solibacter and C. koribacter ). Additionally, both soil bacterial and fungal communities at the Pinbarren site and only fungal community at the Kandanga site were different in the mulch group compared with all other herbicides. The differences persisted 12 months after the cessation of herbicide application at the Pinbarren site. Conclusion Our study suggested that the application of mulch to assist with riparian revegetation would be beneficial for soil microbial functionality. The use of herbicides may have long-lasting effects on soil microbial biomass and diversity and therefore herbicides should be used with caution as part of an integrated land management plan.

Clonal diversity and recruitment strategy of the two dominant seagrass species Cymodocea rotundata and Enhalus acoroides in the southern Philippines - Dan Moywela Arriesgado; Hiroyuki Kurokochi; Elgen Moywela Arriesgado; Elnor Caseres Roa; Ruby C. Gonzales; Delyn Megarbio Bucay; Lyndon Lagrosas Roa; Mayene Perpetua Balaba; Chunlan Lian (Aquatic Botany, 2023)

Minimal vertical transmission of Equid alphaherpesvirus 1 (EHV-1) in normal developing foals during a naturally occurring abortion outbreak - Amjad Khan; Miguel Blanco; Jennifer Janes; Rebecca Ruby; Ioana Popa; Rocio Vicioso; Lutz S Goehring (Journal of Equine Veterinary Science, 2023)

Monitoring ambient air pollution and pulmonary function in asthmatic children by mobile applications in COVID-19 pandemic - Pei-Yu Lin; Jiu-Yao Wang; Bing-Fang Hwang; Ruby Pawankar; I-Jen Wang (International Journal of Hygiene and Environmental Health, 2023)

Prenatal bisphenol A and S exposure and atopic disease phenotypes at age 6 - Abigail Gaylord; Emily S. Barrett; Sheela Sathyanarayana; Shanna H. Swan; Ruby H.N. Nguyen; Nicole R. Bush; Kecia Carroll; Drew B. Day; Kurunthachalam Kannan; Leonardo Trasande (Environmental Research, 2023)

Effectiveness of Non-Pharmacological Interventions for Agitation during Post-Traumatic Amnesia following Traumatic Brain Injury: A Systematic Review - Sarah L. Carrier; Jennie Ponsford; Ruby K. Phyland; Amelia J. Hicks; Adam McKay (Neuropsychology Review, 2023)
Agitation is common in the early recovery period following traumatic brain injury (TBI), known as post-traumatic amnesia (PTA). Non-pharmacological interventions are frequently used to manage agitation, yet their efficacy is largely unknown. This systematic review aims to synthesize current evidence on the effectiveness of non-pharmacological interventions for agitation during PTA in adults with TBI. Key databases searched included MEDLINE Ovid SP interface, PubMed, CINAHL, Excerpta Medica Database, PsycINFO and CENTRAL, with additional online reviewing of key journals and clinical trial registries to identify published or unpublished studies up to May 2020. Eligible studies included participants aged 16 years and older, showing agitated behaviours during PTA. Any non-pharmacological interventions for reducing agitation were considered, with any comparator accepted. Eligible studies were critically appraised for methodological quality using Joanna Briggs Institute Critical Appraisal Instruments and findings were reported in narrative form. Twelve studies were included in the review: two randomized cross-over trials, three quasi-experimental studies, four cases series and three case reports. Non-pharmacological interventions were music therapy, behavioural strategies and environmental modifications, physical restraints and electroconvulsive therapy. Key methodological concerns included absence of a control group, a lack of formalised agitation measurement and inconsistent concomitant use of pharmacology. Interventions involving music therapy had the highest level of evidence, although study quality was generally low to moderate. Further research is needed to evaluate non-pharmacological interventions for reducing agitation during PTA after TBI. Systematic review registration number: PROSPERO (CRD42020186802), registered May 2020.

Improved and reliable plant regeneration and Agrobacterium-mediated genetic transformation in soybean (Glycine max L.) - Ruby Tiwari; Ajay K. Singh; Manchikatla V. Rajam (Journal of Crop Science and Biotechnology, 2023)

Towards Ensemble-Based Kilometer-Scale Climate Simulations over the Third Pole Region - Andreas F. Prein; Nikolina Ban; Tinghai Ou; Jianping Tang; Koichi Sakaguchi; Emily Collier; Sanjay Jayanarayanan; Lu Li; Stefan Sobolowski; Xingchao Chen; Xu Zhou; Hui-Wen Lai; et al. (Climate Dynamics, 2023)

Comparison of efficiency of various DC-DC converters connected to solar photovoltaic module - Krishnaraj Nisha; Ruby Beniwal (Environmental Science and Pollution Research, 2023)

Economic and environmental feasibility of recycling flexible plastic packaging from single stream collection - Yingqian Lin; Michael H. Severson; Ruby T. Nguyen; Anne Johnson; Christopher King; Beth Coddington; Hongqiang Hu; Brennan Madden (Resources, Conservation and Recycling, 2023)

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

Cuscuta reflexa Possess Potent Inhibitory Activity Against Human Malaria Parasite: An In Vitro and In Vivo Study - Sashi Bhusan Ojha; Raj Kumar Sah; Evanka Madan; Ruby Bansal; Shaktirekha Roy; Shailja Singh; Gunanidhi Dhangadamajhi (Current Microbiology, 2023)

Comprehensive Analysis of the Physiological Characterization of Escherichia coli Nissle 1917 - S. Ramadevi; Ruby Shelin; Meenakshi Shanmugaraja (Current Microbiology, 2023)

Late glacial climate evolution in the Patagonian Andes (44–47° S) from alpine glacier modelling - Ruby Muir; Shaun Eaves; Lauren Vargo; Brian Anderson; Andrew Mackintosh; Esteban Sagredo; Rodrigo Soteres (Quaternary Science Reviews, 2023)

Remarkable photocatalytic performances towards pollutant degradation under sunlight and enhanced electrochemical properties of TiO2/polymer nanohybrids - Mariadhas Jarvin; Daniel Rani Rosaline; Thamizharasan Gopalakrishnan; Maniveldoss Beaula Ruby Kamalam; Edson Luiz Foletto; Guilherme Luiz Dotto; Savariroyan Stephen Rajkumar Inbanathan (Environmental Science and Pollution Research, 2023)

The impact of PUFA-enriched yogurt consumption on cardiovascular risk markers: A review - Laura-Natalia Cortés; Ruby-Alejandra Villamil; Lilia-Yadira Cortés (PharmaNutrition, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

Soil Selenium Addition for Producing Se-Rich Quinoa and Alleviating Water Deficit on the Peruvian Coast - Ruby Vega-Ravello; Maria Belen Romero-Poma; Cynthia de Oliveira; Luiz Roberto Guimarães Guilherme; Guilherme Lopes (Journal of Soil Science and Plant Nutrition, 2023)

An integrated supply chain analysis for cobalt and rare earth elements under global electrification and constrained resources - Michael H. Severson; Ruby T. Nguyen; John Ormerod; Sophie Williams (Resources, Conservation and Recycling, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Mathematical insights into the role of dopamine signaling in circadian entrainment - Ruby Kim; H. Frederik Nijhout; Michael C. Reed (Mathematical Biosciences, 2023)

Prevalence and distribution of antimicrobial resistance in effluent wastewater from animal slaughter facilities: A systematic review - Leo Foyle; Matthew Burnett; Abbey Creaser; Rachel Hens; Julia Keough; Lauren Madin; Ruby Price; Hayley Smith; Samuel Stone; Robert T. Kinobe (Environmental Pollution, 2023)

Correction to: Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2023)
The article “Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions”, written by Yun QIAN, TC CHAKRABORTY, Jianfeng LI, Dan LI, Cenlin HE, Chandan SARANGI, Fei CHEN, Xuchao YANG, and L. Ruby LEUNG was originally published electronically on the publisher’s internet portal on 25 of January 2022 with open access. With the author(s)’ decision, the copyright of the article changed from © The Author(s) 2022 to © Battelle Memorial Institute [2022]. The original article has been corrected.

Smart photovoltaic system for Indian smart cities: a cost analysis - Ruby Beniwal; Shruti Kalra; Narendra SinghBeniwal; Hari Om Gupta (Environmental Science and Pollution Research, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Classification of glacier with supervised approaches using PolSAR data - Ruby Panwar; Gulab Singh (Environmental Monitoring and Assessment, 2023)